2013
DOI: 10.4049/jimmunol.1202612
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Equilibrium Is a Balance between Tumor Cell Proliferation and T Cell–Mediated Killing

Abstract: Local failures following radiation therapy are multifactorial and the contributions of the tumor and the host are complex. Current models of tumor equilibrium suggest that a balance exists between cell birth and cell death due to insufficient angiogenesis, immune effects, or intrinsic cellular factors. We investigated whether host immune responses contribute to radiation induced tumor equilibrium in animal models. We report an essential role for immune cells and their cytokines in suppressing tumor cell regrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 33 publications
(48 reference statements)
7
123
0
1
Order By: Relevance
“…These results suggest that anti-PD-L1 treatment not only improves the effects of IR on the primary tumor, but also mediates an abscopal effect on distant tumors. Altogether, these results demonstrate that CD8 + T cells are necessary for the therapeutic effects of IR plus anti-PD-L1 therapy and are in agreement with our previous observations using IR as a single modality (2,3,31). Next, we hypothesized that the combination of IR and anti-PD-L1 treatment enhances tumor antigen-specific T cell responses.…”
Section: Resultssupporting
confidence: 78%
“…These results suggest that anti-PD-L1 treatment not only improves the effects of IR on the primary tumor, but also mediates an abscopal effect on distant tumors. Altogether, these results demonstrate that CD8 + T cells are necessary for the therapeutic effects of IR plus anti-PD-L1 therapy and are in agreement with our previous observations using IR as a single modality (2,3,31). Next, we hypothesized that the combination of IR and anti-PD-L1 treatment enhances tumor antigen-specific T cell responses.…”
Section: Resultssupporting
confidence: 78%
“…Costimulatory and coinhibitory receptors play a dominant role in T-cell activation, differentiation, and function (60). It is reasonable to argue that the agonists and antagonists targeting costimulators/inhibitors are able to increase T-cell function or relieve T-cell inhibition during radiotherapy (14). We have found that the effect of radiation-induced immune-mediated tumor regression gradually diminished as tumor growth continued to progress.…”
Section: Strategies To Enhance Antitumor Immune Response To Improve Rmentioning
confidence: 78%
“…Although radiation is effective in producing tumor regression, the tumors may eventually recur even after a prolonged stable or dormant phase (14). Multiple resistance mechanisms facilitate tumor relapse during the inflammatory response that occurs after radiation.…”
Section: Strategies To Enhance Antitumor Immune Response To Improve Rmentioning
confidence: 99%
See 2 more Smart Citations